Dentists and physiotherapists level of collaboration in the treatment of temporomandibular disorders in France - Loanne Sauvageon; Guillaume Savard; Carol Moussa; Gael Y. Rochefort; Frédéric Denis; Cécile Fossat; Matthieu Renaud (BMC, 2024)
Abstract Objectives Temporomandibular disorders (TMD) affect 10% of the population in France, significantly impacting patient's health and quality of life. The multifactorial etiology of TMD complicates its treatment. Consequently, adopting a multidisciplinary approach that encourages collaboration among healthcare professionals is recommended. Nevertheless, this approach does not seem to occur on a regular basis. The aim of this study was to assess the dentist's treatment support of TMD in the context of the inter-professional collaboration between dental practitioners and physiotherapists. Materiel and methods A cross-sectional observational study was conducted based on an online questionnaire from January 15th to April 30th, 2023. The data are collected through Professional Broad, Regional Unions of Health Professional and Healthcare Professional Communities and Territories. Results Of the 420 responses analyzed, the main first-line treatment provided by the dentist was the correction of dental occlusion (84%). The rate of referral to a physiotherapist was 57% and was 75% for second-placed treatment. The main reason for the lack of referral was a lack of awareness of physiotherapy role in the management of TDM. We observed that 70% of dental health practitioners were interested about inter-professional collaboration and the development of postgraduate training. Conclusion Given the difficulty of managing TDM, efforts should be made to improve inter professional management. Clinical relevance The implementation of appropriate teaching in initial training seems to be essential to allow dentists to open the range of treatment for TMD with increased knowledge of physiotherapy techniques for an adapted prescription to the patient.